Multilocus sequence typing of Neisseria meningitidis directly from cerebrospinal fluid. - Kriz, P. (Cambridge University Press, 2002)
MLST typing of Neisseria meningitidis directly from clinical material was introduced in the National Reference Laboratory for Meningococcal Infections in Prague. Four cerebrospinal fluid samples were obtained from patients with suspected meningococcal invasive disease. In all samples, all classical laboratory methods gave negative results and the only positive method was PCR, which revealed Neisseria meningitidis group C (two specimens) and group B (two specimens), respectively. MLST performed directly from cerebrospinal fluid revealed that the strains causing the two group C infections were of sequence type (ST) 11, while the two group B infections were characterized as ST-32 and ST-33 respectively. Multi-locus sequence typing of meningococci directly from clinical material offers the opportunity to improve further the surveillance of meningococcal disease and has now been introduced into the routine portfolio of tests employed at the national reference laboratory of the Czech Republic.